The Status and Function of English In Indonesia: A Review of Key Factors - Lauder, Allan (Makara Human Behavior Studies in Asia, 2008)
In order to understand the way English is used and seen in Indonesia today, it is useful to know something about how historical, political, socio-cultural and linguistic factors have shaped its status and functions over the last century. The use of English in Indonesia has developed in the context of post-colonial educational competency building, and more recently the need to support development – in particular its role in state education. However, attitudes of some policy makers and commentators towards the language have often been ambivalent, expressing fears of its power to exert negative cultural influences. The special status of English as a global language with many potential varieties that might pose as models for Indonesia also poses the question of which one would be right for the country. The paper looks at these educational and policy issues, and also gives some suggestions about the future.